FORMATION OF FINANCIAL LITERACY OF STUDENTS OF FUTURE MATHEMATICS TEACHERS BY SOLVING KEYS - Urunov Nomonjon Moydinovich; Askarov Abrorjon Hayitmirzaevich; Mirhamidova Gulibonu Mirabdullojon Qizi (Scholar Express Journals, 2024)
In modern conditions, financial literacy can be formed on the basis of the idea of interdisciplinary integration. Interdisciplinary integration can be defined as one aspect of educational activity that connects general education and professional Sciences to a single complex. A distinctive feature of this complex is the formation in the student of a qualitatively new system of holistic knowledge and skills, which, in contrast to the components included in the system, are assigned to new integral features. Consequently, the presence of elements that shape positive financial behavior in students is necessary in the structure of educational activities of educational organizations. It is relevant for students of higher educational institutions to form skills for the practical application of fundamental and special knowledge in making economic decisions (in personal, family, Professional, Scientific and social activities)
Keywords: Professional; Scientific and social activities